2010
DOI: 10.1042/ba20090277
|View full text |Cite
|
Sign up to set email alerts
|

Production of rhamnolipid biosurfactants by Pseudomonas aeruginosa DS10‐129 in a microfluidic bioreactor

Abstract: A low-cost microBR (microbioreactor) made from PTFE [poly(tetrafluoroethylene)] was used to cultivate a model organism, Pseudomonas aeruginosa DS10-129. The progress of bioprocessing was monitored by comparing the growth of the organism in a microBR, a conventional bench scale bioreactor and a shake flask. Under the microBR conditions, the organism produced 23 mg/ml of pyocyanin that had antimicrobial effects against Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas teessidea an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…DiRLs are generally the most abundant types of RLs produced (Monteiro et al 2007;Mata-Sandoval et al 2001;Samadi et al 2012;Rahman et al 2010) with only a few studies reporting mono-RLs as the predominant RL species (Arino et al 1996;Sim et al 1997). Some Pseudomonas strains have been reported to produce mono-RLs only (Zhang and Miller 1992;Gunther et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…DiRLs are generally the most abundant types of RLs produced (Monteiro et al 2007;Mata-Sandoval et al 2001;Samadi et al 2012;Rahman et al 2010) with only a few studies reporting mono-RLs as the predominant RL species (Arino et al 1996;Sim et al 1997). Some Pseudomonas strains have been reported to produce mono-RLs only (Zhang and Miller 1992;Gunther et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Read et al ( 1992 ) also showed the presence of 65 μl/ml rhamnolipid in the secretions of a lung removed from a cystic fi brosis patient. The cytotoxic and haemolytic effects of crude rhamnolipids from other rhamnolipid producers have been demonstrated by researchers (Häussler et al 1998(Häussler et al , 2003Rahman et al 2010 ). Rhamnolipids have been shown to be heat-stable haemolysins having haemolytic activity on various erythrocyte species ( Fujita et al 1988 ;Johnson and Boese-Marrazzo 1980 ) and cytotoxic at high concentration to immune cells (Bjarnsholt et al 2005 ;Jensen et al 2007 ).…”
Section: Rhamnolipidsmentioning
confidence: 88%
“…Novel natural producers of rhamnolipids identifi ed as P. clemancea nov. and P. teessidea nov. have been reported by Rahman et al ( 2010 ). Rhamnolipid production can be achieved with Pseudomonas sp.…”
Section: Rhamnolipidsmentioning
confidence: 92%
“…The presence of characteristic adsorption bands at 1377 cm -1 , 1458cm -1 , 2854 cm -1 , 2870 cm -1 , 2924 cm -1 and 2953 demonstrated the presence of aliphatic long hydrocarbon chain which was endorsed by Rahman et al (2010). The strong absorbance at 3401 cm -1 was considered as the characteristic peak of glycolipid biosurfactants (Li et al, 2002) which was assigned to the C-H stretching vibrations of the hydrocarbon chain positions.…”
Section: Discussionmentioning
confidence: 99%